Thickness‐Dependent Refractive Index of 1L, 2L, and 3L MoS2, MoSe2, WS2, and WSe2. Issue 13 (6th May 2019) - Hsu, Chunwei; Frisenda, Riccardo; Schmidt, Robert; Arora, Ashish; de Vasconcellos, Steffen Michaelis; Bratschitsch, Rudolf; van der Zant, Herre S. J.; Castellanos‐Gomez, Andres
Abstract: An interesting aspect of 2D materials is the change of their electronic structure with the reduction of thickness. Molybdenum and tungsten‐based transition metal dichalcogenides form an important family of 2D materials, whose members show a thickness‐dependent bandgap and strong light–matter interaction. In this work, the experimental determination of the complex refractive index of 1‐, 2‐, 3‐layer thick MoS2, MoSe2, WS2, and WSe2 in the range from 400 to 850 nm of the electromagnetic spectrum is reported by using microreflectance spectroscopy and combined with calculations based on the Fresnel equations. It is further provided a comparison with the bulk refractive index values reported in the literature and a discussion of the difference/similarity between our work and the monolayer refractive index available from the literature, finding that the results from different techniques are in good agreement. Abstract : Mo‐ and W‐based transition metal dichalcogenides form an important family of layered materials with a strong dependency of the bandgap energy on the thickness. In this work, the experimental determination of the complex refractive index of 1‐, 2‐, 3‐layer thick MoS2, MoSe2, WS2, and WSe2 in the range from 400 to 850 nm of the electromagnetic spectrum is reported.